Current Status of Knowledge on Tumor Patterns in Sudan's Eastern Darfur State - Mudather Elnoor Younis; Fadwa Mohamed Ibrahim; Saeed Hassan Saeed; Mohamed Elhaj Abdurrahman; Abu baker Mohamed Yahya (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
One of the major causes of death in the globe is cancer. According to estimates, the number of people affected by cancer worldwide will continue to rise, reaching 21.4 million new cases and 13.2 million deaths by 2030.This study was carried out in the Sudanese state of East Darfur and it is a retrospective in nature. Clinical and Public Health Laboratory provided results, were collected, gathered then analyzed. The Statistical Package for Social Science (SPSS) version 25 was used evaluate demographic data and tumor cases. show that 87.3% of patients who were affected by were females, while only 12.7% of patients were males show that 15.87% of patients whom affected were 33 years old, followed by 9.52% their age were 34 and 45 years old endometritis accounted for (19.05% ) of the abnormalities that affected the patients, followed by ovaries (14.29%), endometrial polyps (12.70%), Breast masses (7.94%), chronic endometritis, prostatic hyperplasia The data on the present status of the most common benign and malignant tumors in Sudan and the neighboring areas is scarce. There is a complex interaction between the impact of infectious agents, genetics and environmental risk factors on the risk of development of most of these tumors.